Transient Global Amnesia Linked to Impairment of Brain Venous Drainage: An Ultrasound Investigation - Han, Ke; Hu, Han-Hwa; Chao, A-Ching; Chang, Feng-Chi; Chung, Chih-Ping; Hsu, Hung-Yi; Sheng, Wen-Yung; Wu, Jiang (Frontiers in Neurology, 2019)
Background: Previous neuroimaging and ultrasound studies suggested that compression and stenosis of the internal jugular vein (IJV) in patients with transient global amnesia (TGA) may impair IJV drainage, while a patent IJV releases intracranial pressure caused by the Valsalva maneuver (VM). Methods: Seventy-nine TGA patients with complete ultrasound examination data during admission were recruited prospectively to evaluate IJV drainage, which included the time-averaged mean velocity, and the cross-sectional lumen area of the IJV at the vein’s middle (J2) and distal (J3) segments and the cross-sectional area during a 10-s VM to test for any retrograde or anti-grade flow. Forty-five TGA patients and 45 age- and sex-matched control subjects underwent complete contrast-enhanced magnetic resonance (MR) venous studies, which included time-resolved imaging of contrast kinetics, contrast-enhanced axial T1-weighted MR imaging, and phase-contrast-based non-contrast enhanced magnetic resonance venography (MRV). Results: In those subjects with complete MRV studies, the flow volumes exhibited at both the J2 and J3 segments of the left IJV and left vertebral vein (VV) were significantly lower in the TGA patients than in the control subjects. Although there was no significant difference in the flow volume of right IJV, the total of bilateral IJV and VV flow volumes was still significantly lower in the TGA patients. As compared with the control subjects, the TGA patients exhibited significantly higher prevalence of completely blocked right IJV drainage at the J3 segment during the VM, but non-significantly higher for the left IJV at the J3 segment and for the right IJV at the J2 segment. Conclusion: Our results confirmed that the total venous flow decreases in the IJVs and VVs of the patients with TGA. This is consistent with the findings of previous MR imaging studies that have reported about compression and stenosis of the draining veins. We also found that IJV drainage is relatively compromised during the VM in the patients with TGA.